GIS-Based Mapping of Water Ponding Areas in Residential Zones of Lamongan District, Indonesia - Julian Tri Kurnia Utomo; Hendrata Wibisana; Bagas Aryaseta (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Residential water ponding has become a recurring problem in Lamongan District, Indonesia, disrupting residential activities and increasing flood risk. Accurate spatial identification of vulnerable areas is essential to support effective urban planning and drainage management. This study aims to map residential water ponding vulnerability using a Geographic Information System (GIS) and the Weighted Overlay Analysis. Five parameters, namely rainfall, slope, soil type, land use, and drainage conditions, were processed using ArcGIS through scoring, weighting, and spatial overlay techniques. A field questionnaire survey was also conducted to validate the spatial analysis results. The analysis classified the study area into four vulnerability levels: Low, Moderate, High, and Very High. The High vulnerability class dominated the study area, covering 37.14%, followed by Moderate (32.90%), Very High (25.41%), and Low (3.64%). Questionnaire results confirmed that water ponding frequently occurs in several residential areas, with respondents identifying high rainfall, inadequate drainage capacity, and blocked drainage channels as the primary contributing factors. The consistency between GIS analysis and field observations indicates that the proposed approach provides reliable spatial information for identifying priority areas for flood mitigation. The resulting vulnerability map can support evidence-based urban planning and sustainable drainage management in Lamongan District. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land